A perspective on thermal application and the direct conversion of solar energy in rural areas in Brazil (Research, Society and Development, 2021)
The need to reduce the effects of global warming and extend the supply of electricity in geographically isolated rural areas, governments have encouraged the use of alternative sources of electricity generation by public policies. In this scenario, solar energy stands out, originating from the radiation emitted by the sun, which can be used as a thermal source for the fluids or environments heating and can be directly converted into electrical energy, based on the thermoelectric and photovoltaic effects. The aim of this study is to approach a qualitative generic review of the thermal and photovoltaic use of solar energy in rural areas in Brazil in the last twelve years (2009 to 2020). Consequently, the current advances of this alternative source in the national electric matrix and the incentive public policies to decentralized technologies of electricity production were highlighted. To create the literature review, the study used information published in scientific papers, books, atlases and normative regulations that met a series of basic selection criteria. The results showed that solar thermal energy has been used for the water treatment and desalination for human consumption, reuse in agricultural production, in addition to drying grains, fruits and residues of rural products. In other hand photovoltaic solar energy has been used for pumping water with a focus on supplying beef cattle and precision irrigation, in addition to rural electrification, a topic of great prominence in Brazil. Government incentives helped to unify efforts regarding rural electrification, expanding the number of isolated regions with electricity supply.